Experimental study of vibration control in a 3 DOF pitch-plane model of an MR vehicle suspension - Sapiński, Bogdan; Martynowicz, Paweł (Wydawnictwa AGH, 2007)
The paper is concerned with the experimental study of vibration control in a vehicle suspension model equipped with independently controlled magnetorheological (MR) dampers in front and rear sections of the vehicle body, and in the driver's seat suspension. Pitch-plane suspension model with one pitch degree of freedom (DOF) and two bounce DOFs was considered. The system was tested under harmonic excitations with an open loop and feedback. Performance of standard skyhook controller was compared with cascade controllers, in which the reference resistance forces determined by linear-quadratic or skyhook principles were fed to the inverse model of an MR damper. The tests were conducted in the experimental setup with measurement and control system configured in MATLAB/Simulink environment.

W artykule przedstawiono analizę eksperymentalną układu sterowania drganiami modelu zawieszenia pojazdu wyposażonego w niezależnie sterowane tłumiki magnetoreologiczne (MR) umiejscowione w przednim i tylnym zawieszeniu nadwozia pojazdu, oraz w zawieszeniu fotela kierowcy/operatora. Rozważono płaski model zawieszenia posiadający jeden stopień swobody związany z przechyłem wzdłużnym oraz dwa stopnie swobody związane z przemieszczeniem pionowym. Przeprowadzono badania układu otwartego oraz układu zamkniętego przy wymuszeniach harmonicznych. Dokonano porównania działania regulatora typu skyhook z regulatorami kaskadowymi, dla których referencyjne siły oporu uzyskane jako wyjścia algorytmu skyhook lub rozwiązania problemu liniowo-kwadratowego były odwzorowywane z wykorzystaniem modelu odwrotnego tłumika MR. Badania przeprowadzono na stanowisku laboratoryjnym z wykorzystaniem układu pomiarowo-sterującego skonfigurowanego w środowisku MATLAB/Simulink.
Sterowanie drganiami płaskiego modelu zawieszenia pojazdu o trzech stopniach swobody - analiza eksperymentalna
Mechanics
References. s. 123-124.
Keywords: MR damper; pitch-plane suspension model; vibration control; tłumik MR; płaski model zawieszenia; sterowanie drganiami